Curricula, Teaching Methods, and Success Metrics of Clinician–Scientist Training Programs: A Scoping Review. (1st June 2022) - Li, Queenie K.W.; Wollny, Krista; Twilt, Marinka; Walsh, Catharine M.; Bright, Katherine; Dimitropoulos, Gina; Pires, Linda; Pritchard, Lesley; Samuel, Susan; Tomfohr-Madsen, Lianne
Abstract : Purpose: To describe the literature on clinician–scientist training programs to inform the development of contemporary and inclusive training models. Method: The authors conducted a scoping review, searching the PubMed/MEDLINE, CINAHL, and Embase databases from database inception until May 25, 2020. Studies presenting primary research that described and evaluated clinician–scientist training programs were identified for data abstraction. On the basis of deductive and inductive methods, information about program characteristics, curricula, teaching strategies, and success metrics was extracted. The extracted variables were analyzed using descriptive statistics. Results: From the initial 7, 544 citations retrieved and 4, 974 unique abstracts screened, 81 studies were included. Of the 81 included studies, 65 (80.2%) were published between 2011 and 2020, 54 (66.7%) were conducted in the United States, and 64 (79.0%) described programs that provided broad clinician–scientist training. Few programs provided funding or protected research time or specifically addressed needs of trainees from underrepresented minority groups. Curricula emphasized research methods and knowledge dissemination, whereas patient-oriented research competencies were not described. Most programs incorporated aspects of mentorship and used multiple teaching strategies, such as direct and interactive instruction. Extrinsic metrics of success (e.g., research output) were dominant in reported program outcomes compared with markers of intrinsic success (e.g., career fulfillment). Conclusions: Although programs are providing clinician–scientists with practical skills training, opportunities exist for curricular and pedagogic optimization that may better support this complex career path. Training programs for clinician–scientists can address contemporary issues of wellness and equity by reconsidering metrics of program success and evolving the core tenets of their education models to include equity, diversity, and inclusion principles and patient-oriented research competencies.